A Case-Control Study on the Take-Off Sign in Lesional Skin Biopsies of Patients with Pityriasis Rosea - Antonio An Tung Chuh; Vijay Zawar; Gayatri Karad (Iranian Society of Pathology, 2016)
Dear Editor-in-Chief   Lesional histopathological features in pityriasis rosea (PR) are non-specific (1).  Our aim here is to investigate whether a histopathological take-off sign (TOS) is associated with PR.